Current Ecological Restoration Plans in Latin America: Progress and Omissions - Méndez-Toribio, Moisés (2017)
The Aichi 15 goal of the Convention on Biological Diversity, the Bonn Challenge, and the Initiative 20x20 are initiatives aimed at fostering restoration in Latin America; however, they are efforts that do not specify restoration processes. In this study, the countries having a restoration plan in Latin America were identified to analyze later the scope of the plans. The countries with restoration plans were Brazil, Colombia, Ecuador and Guatemala. The analysis showed that their objectives and restoration approaches coincide. It is outlined the consideration of setting objectives for recovering ecosystemic services in a sustainable way, as well as the adoption of long term and landscape-scale restauration approaches. The assistance of ecological succession is considered as a cost-effective way for restoration. Social participation is important for the construction and operation of initiatives, and a legal framework associated with the plans already exists. However, it is necessary for the philosophical framework of the plans to be strengthened, for socio-economic criteria and those of success to be included to the prioritization of areas, and for the ascending approaches to be developed in the restoration processes that benefit their financing. Protocols for monitoring biophysical and socioeconomic aspects of restoration should be included in the plans. The plans under consideration are a major step to comply with international commitments. However, the challenge will not only be to consolidate such instruments, but also ensure that the elements of these instruments allow the large scale recovery of systems.